149k views
0 votes
Which equation has no solution?

A.
-4(y + 7) = 2(-2y − 9) − 10
B.
-2(2y + 8) = 4y + 5 + y
C.
4(y + 9) = -4(y − 9)
D.
3y + 5 − 7y = 4(-y + 1) + 5

User Feliks
by
5.4k points

2 Answers

1 vote

Answer:

D. 3y + 5 − 7y = 4(-y + 1) + 5

Explanation:

User PropellerHead
by
5.5k points
7 votes

Answer: D. 3y + 5 − 7y = 4(-y + 1) + 5

Explanation:

Original equation:

3y + 5 - 7y = 4(-y+1) + 5

Group like terms on the left of the equal sign and distribute on the right side of equal sign:

-4y + 5 = (-4y +4) + 5

Simplify:

-4y + 5 = -4y +9

Subtract 5 from both sides:

-4y = -4y + 4

Add 4y to both sides:

0 = 4

0 CANNOT equal 4 therefore, this equation has no solution.

User AllmanTool
by
4.7k points